Characteristics of pathology and transcriptome profiling reveal features of immune response of acutely infected and asymptomatic infected of carp edema virus in Koi - Ouyang, Ping; Ren, Yongqiang; Zhou, Yongheng; Li, Qiunan; Huang, Xiaoli; Chen, Defang; Geng, Yi; Guo, Hongrui; Fang, Jing; Deng, Huidan; Lai, Weiming; Chen, Zhengli; et al. (Frontiers in Immunology, 2023)
Koi sleepy disease (KSD) was a high mortality and infection viral disease caused by carp edema virus (CEV), which was a serious threat to aquaculture of common carp and export trade of koi worldwide. Asymptomatic infections can be activated under appropriate a condition is one of the most important reasons to make KSD difficult for prevention and spread worldwide. However, the understanding of the molecular correlates of these infections is still unknown. The purpose of this study was to compare the pathology change, enzyme activity, immunoglobulin activity, host and viral gene expression differences in acutely infected, dead and cohabiting asymptomatic koi infected with CEV. Healthy koi were used as a control. The gross pathology, histopathology and ultrastructural pathology showed the difference and characteristics damage to the tissues of Koi under different infection conditions. PAS staining, enzyme activity and immunoglobulin activity revealed changes in the immune response of gill tissue between acutely infected, dead, asymptomatic infected and healthy koi. A total of 111 and 2484 upregulated genes and 257 and 4940 downregulated genes were founded in healthy koi vs asymptomatic infected koi and healthy koi vs acutely infected, dead koi, respectively. Additionally, 878 upregulated genes and 1089 downregulated genes were identiﬁed in asymptomatic vs. acutely infected, dead koi. Immune gene categories and their corresponding genes in different comparison groups were revealed. A total of 3、59 and 28 immune-related genes were identified in the group of healthy koi vs asymptomatic infected koi, healthy koi vs acutely infected, dead koi and asymptomatic infected koi vs acutely infected, dead koi, respectively. Nineteen immune-related genes were co-expressed both in healthy koi vs acutely infected, dead Koi and asymptomatic Koi vs acutely infected, dead Koi, while 9 immune-related genes were differentially expressed only in asymptomatic koi vs acutely infected, dead Koi, which may play a role in viral reactivation. In conclusion, the data obtained in this study provide new evidence for further elucidating CEV-host interactions and the CEV infection mechanism and will facilitate the implementation of integrated strategies for controlling CEV infection and spread.